Re-motivation and Resilience Factorability Among English Language Learners at University Level - nazirullah (Journal of Peace, Development and Communication, 2022)
Re-motivation and coping strategies are external and internal factors that strengthen undergraduate students' motivational foundation in an English language learning environment. This study used a quantitative research approach, and data was collected from Kohat University students (N=220). Descriptive and inferential statistical methods were adopted for the statistical measurement. Students' L2 learning was shown to be impacted by the resilience of those who were re-motivated. Student resilience, rebounding from setbacks, motivated behavior, effort, desired proficiency, and satisfaction were all influenced by a re-motivational component in research. It was concluded that the most crucial personality re-motivating students' attitudes is English language teachers. The studies put forward recommendations to the policymakers that teachers or instructors should re-motivate their English language students in the classroom.